Gaslight - Hamilton, Patrick 1904-1962; Addinsell, Richard 1904-1977 (BFI, 2013)
"Zwanzig Jahre nach dem Mord an einer alten Dame bezieht der Mörder mit seiner jungen Frau das Haus, in dem die Bluttat geschah. Er will die kostbaren Rubine finden, die dort versteckt sein sollen. Zu diesem Zweck versucht er, seine Frau systematisch in den Wahnsinn zu treiben, wird aber an der Durchführung seines Plans durch einen Detektiv von Scotland Yard gehindert. Im viktorianischen London spielender Psychothriller, der vor allem durch eine effektvolle Kameraarbeit eine wohlig bedrohliche Atmosphäre schafft." ][filmdiendt.de]
Original: Großbritannien 1940
Special features: presented in both High Definition and Standard Definition ; "Spanish A B C" (Thorold Dickinson, Sidney Cole, 1938, 20 min): a short film on the Republican efforts to improve education standards during the Spanish Civil War ; "Behind the Spanish lines" (Sidney Cole, Thorold Dickinson, 1938, 20 min): a companion piece to "Spanish A B C" which looks at life in the Republican zone ; "Westward Ho!" (Thorold Dickinson, 1940, 9 min): a short film to promote the evacuation of urban children to rural areas ; "Miss Grant goes to the door" (Brian Desmond Hurst, 1940, 7 min): a short film about a German invasion from a story by Dickinson ; "Yesterday is over your shoulder" (Thorold Dickinson, 1940, 9 min): a short film encouraging unskilled workers to join free, government organised, engineering training schemes ; original promotional materials and documents from the BFI National Archive (downloadable PDFs, DVD only).
Keywords: Film